The Effect of Layering Superhydrophobic Coating On Its Transmittance, Durability and Self-Cleaning Properties - NIK MOHD NASER, NIK AMINUDDIN; Ameruddin, Amira Saryati (Enhanced Knowledge in Sciences and Technology, 2022)
Two superhydrophobic solution were prepared onto the glass slides which were S Nano hydrophobic liquid repellent and DPRO super hydrophobic glass coating by using wipe method which the best option that can be used to apply on the glass substrate of the solar panel. The coated glass slides were characterized using Field Emission Scanning Electron Microscopy (FESEM), contact angle meter and UV-Vis spectrophotometer. Based on the characterization, all coatings show hydrophobic properties and the transmittance value is above 80% allowing light to pass through the glass.  The water contact angle were in the range of 111º to 117 º while DPRO super hydrophobic glass coating was in range of 107 º to 108 º. For further characterization, the samples were tested for their durability through sandpaper abrasion.  The coatings also shows that it was able to self-clean washed out all of the kaolin powder that lies on its path. The water contact angle of the coatings was analysed again by using in order to find out the coatings’ durability. Based on the findings, both solution shows little changes after the sand paper abrasion test. However, the S Nano hydrophobic solution shows a slightly higher water contact angle showing a better hydrophobic property.